Shocks, household consumption, and livelihood diversification: a comparative evidence from panel data in rural Thailand and Vietnam - Duy Linh Nguyen; Trung Thanh Nguyen; Ulrike Grote (Economic Change and Restructuring, 2022)
We examine the roles of land and labor diversification in mitigating the effects of covariate and idiosyncratic shocks in the two middle-income countries Thailand and Vietnam. We use an unbalanced panel dataset of rural households obtained from five survey waves during 2007–2016 (9291 households for Thailand and 9255 households for Vietnam). We employ the System-Generalized Method of Moments estimators to control for endogeneity. Our study finds that (i) rural households in both countries are able to maintain per capita consumption in the face of idiosyncratic shocks but not covariate shocks; (ii) labor diversification in Thailand and land diversification in Vietnam are used as ex-post coping strategies against covariate shocks but their shock-mitigating roles are insignificant; and (iii) land diversification in Thailand and labor diversification in Vietnam are helpful in improving per capita consumption when households face covariate shocks. Our findings suggest that facilitating access to credit, enhancing farm mechanization, and improving road quality in Thailand as well as promoting the development of local rural nonfarm sectors in Vietnam would benefit rural households in dealing with covariate shocks.
Keywords: 330; Diversification; Covariate and idiosyncratic shocks; Household consumption; System-generalized method of moments